Low Salivary Testosterone Level Is Associated With Efficient Attention Holding by Self Face in Women - Doi, Hirokazu; Shinohara, Kazuyuki (Frontiers in Behavioral Neuroscience, 2019)
Capacity to recognize one’s own face (hereinafter referred to as self face) is a fundamental component of various domains of social cognition such as empathy in humans. Previous research has demonstrated that a high level of androgen suppresses empathic behavior and social brain function. Taking these into consideration, we hypothesized that people with high androgen level show reduced response to self face. The present study examined this hypothesis by investigating the association between attentiveness towards self face, as assessed by a psychophysiological experiment, and salivary testosterone concentration. The attentional responses to self face was measured by a modified Go/NoGo task. In this task, self face or unfamiliar other’s face was presented simultaneously with Go or NoGo signal. In go trials, participants had to divert their attention from the face to a peripheral target. The reaction time (RT) for peripheral target detection in each condition was measured. In addition to behavioral data, saliva samples were collected to assay salivary testosterone concentration. The index of potency of self face to hold viewer’s attention that was computed based on RT data was regressed against salivary testosterone concentration in men and women separately. The analyses revealed that self face holds visuospatial attention more effectively in women with low than high salivary testosterone level, but no such trend was observed in men. This pattern of results indicates that low testosterone level is associated with a pronounced response to self face as we hypothesized and raises the possibility that multiple aspects of self-face processing are under the influence of endocrinological function.